Green Pension Investment: A Dynamic Relationship and Efficiency for the Green Economy in Indonesia - Lestari, Irna Puji; Pambekti, Galuh Tri (Faculty of Economics and Business, Universitas Gadjah Mada, 2025)
Introduction/Main Objectives: This study aims to propose alternative investments from pension funds that are integrated with renewable energy productivity to boost green economic growth in Indonesia.To see the ideal efficient proportion of this investment and renewable energy on a regional scale, the efficiency of green economic performance is also identified. Background Problems: Investments in the green sector are less attractive to pension fund institutions while they have great potential financial sources. These investments should be promoted to support Indonesia's commitment to strengthening multilateral financing to support climate action in developing countries. Novelty: This study will be the first to simulate a green-based investment scheme involving pension funds for green economic growth, as well as capture its level of efficiency in a regional context. Research Methods: Two methods were conducted: the generalized method of moment (GMM) and the data envelopment analysis (DEA). Panel data from 34 provinces in Indonesia were used covering the period of 2016-2022. Finding/Results: The first finding revealed the short and long-term relationship between the green economy, green pension investment, and renewable energy. The second finding revealed that green economy efficiency in Indonesia has a moderate score with the highest score obtained by DKI Jakarta province. Conclusion: Green pension investment could promote the green economy and its efficiency in Indonesia, especially through active integration with the productivity of renewable energy